Visualization of clustered IgE epitopes on alpha-lactalbumin - Hochwallner, H.; Schulmeister, U.; Swoboda, I.; Focke-Tejkl, M.; Civaj, V.; Balic, N.; Nystrand, M.; Härlin, A.; Thalhamer, J.; Scheiblhofer, S.; Keller, W.; Pavkov, T.; et al. (J Allergy Clin Immunol, 2010)
alpha-Lactalbumin (alpha-La) is a major cow's milk (CM) allergen responsible for allergic reactions in infants.|We performed molecular, structural, and immunologic characterization of alpha-La.|Recombinant alpha-lactalbumin (ralpha-La) was expressed in Escherichia coli, purified to homogeneity, and characterized by means of mass spectrometry and circular dichroism, and its allergenic activity was studied by using microarray technology, as well as in a basophil histamine release assay. IgE epitope mapping was performed with synthetic peptides.|According to circular dichroism analysis, ralpha-La represented a folded protein with a high thermal stability and refolding capacity. ralpha-La reacted with IgE antibodies from 57.6% of patients with CM allergy (n = 66) and induced the strongest basophil degranulation with sera from patients with CM allergy who had exhibited gastrointestinal symptoms or severe systemic reactions on CM exposure. ralpha-La contained sequential and conformational IgE epitopes. Superposition of IgE-reactive peptides onto the 3-dimensional structure of alpha-La revealed a close vicinity of the N- and C-terminal peptides within a surface-exposed patch.|ralpha-La can be used for the diagnosis of patients with severe allergic reactions to CM and serves as a paradigmatic tool for the development of therapeutic strategies for CM allergy.
Keywords: Animals Cattle Cells; B-Lymphocyte Escherichia coli Feasibility Studies Histamine Release Humans Immunoglobulin E Lactalbumin Mass Spectrometry Microarray Analysis Milk Hypersensitivity Peptide Fragments Recombinant Proteins; Cultured Circular Dichroism Cloning; Molecular Epitopes